No footprints, past perfect, continuous present: Emilio Olmos Square, Rio Cuarto, Argentina - Carbonari, Mabel (2023)
The article refers to a central square in the city of Rio Cuarto, Córdoba (Argentina) and through the historical journey reveals its past. Layers that identify from their origins to the presentthe different temporalities that materialized in the premises of the current square.From the Monte de los Gauchos, and the successive interventions on the same site: Mercadodel Progreso, Communal House with Civic Plaza, with its three buildings, takes us to differenthistorical moments of which little remains in the memory of citizens.And so, a city overwhelmed by progress, does not preserve what it does not know, by canceling its memory and identity again and again.